Nutritional status of mid-day meal program on government and private school students: a comparative study - Souza, Sunitha H. D.; Shetty, Prashanth; Shetty, Geetha B. (International Journal Of Community Medicine And Public Health, 2021)
Background: Mid-day meal scheme is a school meal programme of the Government of India, designed to improve the nutritional status of school-age children. Malnourished children will not attain optimum potential for growth and development and this affects their physical capacity to work and physiological changes in the later phase of life. The food that we eat affects the nutritional status; hence the study was evaluated to find the nutritional status of the mid-day meal program in school going children. Methods: Total of 100 subjects were selected into 2 groups, 50 students from government schools and another 50 from private schools. Government school groups received mid-day meal scheme and private school students brought their personal lunch. Anthropometric and haemoglobin evaluation was done. Results: The study showed that mid-day meal effects on nutritional status and one meal gives a calorific value of 357.6 and there was a significant difference between the distribution of MUAC (CM) during pre and post nutritious period in government school students. There was no significant difference between the other anthropometric measurements like height, weight and TSFT and hemoglobin values. Conclusions: Study showed that mid-day meal affects nutritional status. A balanced freshly cooked meal in the noon is healthier and nutritious impacting the school children’s academic performance.